2010
DOI: 10.1111/j.1471-0528.2009.02492.x
|View full text |Cite
|
Sign up to set email alerts
|

Improved survival in pregnancy and pulmonary hypertension using a multiprofessional approach

Abstract: Objective Pregnancy in women with pulmonary hypertension (PH) is reported to carry a maternal mortality rate of 30-56%. We report our experience of the management of pregnancies using a strategy of early introduction of targeted pulmonary vascular therapy and early planned delivery under regional anaesthesia.Design Retrospective observational study.Setting Specialist quaternary referral pulmonary vascular unit.Population Nine women with PH who chose to proceed with ten pregnancies.Methods A retrospective revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
114
1
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(120 citation statements)
references
References 34 publications
(44 reference statements)
2
114
1
3
Order By: Relevance
“…Therefore, ES is regarded as an absolute contraindication for pregnancy [8]. If a woman with ES chooses to continue with pregnancy, oxygen therapy, aggressive use of pulmonary vasodilator therapies, and care by a specialist multidisciplinary team may help to minimize mortality [11]. …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, ES is regarded as an absolute contraindication for pregnancy [8]. If a woman with ES chooses to continue with pregnancy, oxygen therapy, aggressive use of pulmonary vasodilator therapies, and care by a specialist multidisciplinary team may help to minimize mortality [11]. …”
Section: Discussionmentioning
confidence: 99%
“…performed a systematic review of all cases of pregnancy-related death in patients with IPAH, congenital heart disease associated with PAH (CHD-PAH), or PAH associated with other diseases (APAH) published between (1997 and 2007) and compared it with data published between 1978 and 1996 to find out whether there has been any progress made in pregnancy outcome among women with PH using newer therapies. [24] The authors observed that mortality remains prohibitively high, though appears to have decreased more recently with the use of new treatments in all three major subgroups (IPAH from 30% to 17%; CHD-PAH 36% to 28%; APAH 56% to 33%), [Table 1]. Most patients died in the 1 st month after delivery in both series.…”
Section: Prognosis Of Pregnancy In Patients With Pulmonary Hypertensionmentioning
confidence: 99%
“…There was no fetal or maternal mortality during pregnancy or in early postpartum period. [24] Another multicenter prospective study of 26 pregnancies showed better outcome with 16 (62%) patients delivering normal healthy babies without complications. Three (12%) patients died and one required urgent heart-lung transplantation.…”
Section: Prognosis Of Pregnancy In Patients With Pulmonary Hypertensionmentioning
confidence: 99%
“…[305354] Nevertheless, maternal mortality remains prohibitively high especially in those with uncontrolled PH. [303254] Thus, pregnancy is discouraged and contraception advice becomes critical in women of child bearing potential who have PH.…”
Section: Pulmonary Hypertension In Pregnancymentioning
confidence: 99%
“…[56] The optimal mode of delivery (vaginal versus caesarean section) and best anesthetic approach (epidural versus general) remain controversial. [30325053545557] Although promising, the effects of advanced PH therapies on pregnancy outcomes remain largely unknown. [30] Endothelin receptor antagonists (including bosentan, ambrisentan and macitentan) are contraindicated during pregnancy due to potential teratogenic effects.…”
Section: Pulmonary Hypertension In Pregnancymentioning
confidence: 99%